Mechanical behavior of polymer-based vs. metallic-based bioresorbable stents - Ang, Hui Ying (2019)
Bioresorbable scaffolds (BRS) were developed to overcome the drawbacks of current metallic drug-eluting stents (DES), such as late in-stent restenosis and caging of the vessel permanently. The concept of the BRS is to provide transient support to the vessel during healing before being degraded and resorbed by the body, freeing the vessel and restoring vasomotion. The mechanical properties of the BRS are influenced by the choice of the material and processing methods. Due to insufficient radial strength of the bioresorbable material, BRS often required large strut profile as compared to conventional metallic DES. Having thick struts will in turn affect the deliverability of the device and may cause flow disturbance, thereby increasing the incidence of acute thrombotic events. Currently, the bioresorbable poly-l-lactic acid (PLLA) polymer and magnesium (Mg) alloys are being investigated as materials in BRS technologies. The bioresorption process, mechanical properties, in vitro observations and clinical outcomes of PLLA-based and Mg-based BRS will be examined in this review.